Exploring the research culture in the health information management profession in Australia. (19th October 2019) - Kemp, Trixie; Finlayson, Lara; Chan, Jaclyn; Lackey, Gavin; Richards, Dwayne; Rupnik, Cassandra; White, Heather; Butler‐Henderson, Kerryn; Low, Sarah
Abstract: Background: Research is an important activity that informs knowledge and practice. The research culture within the Australian Health Information Management (HIM) profession has not been previously reported. Objective: This study explored the perceptions of HIM practitioners about research in their role to establish if there is a research culture in the Australian HIM profession. Method: An online survey was distributed to the HIM community using a snowball recruitment strategy. Results: Of the 149 respondents, more than half (54%) identified they possessed research skills from prior education, whilst 40% considered they had a strong knowledgebase in conducting research. However, only a quarter of respondents indicated that they should undertake research in their role. Barriers to undertaking research included recognition, organisational support and time. Discussion: The findings from this study reflected other studies within clinical workforces. The lack of recognition and support to incorporate research into practitioner roles has implications for the profession and its body of knowledge. Conclusion: Advocating for research to be incorporated into practitioner roles is required to inform knowledge and practice. Increased professional development opportunities may create a stronger research culture within the HIM profession in Australia and strengthen the position of the profession within health.